China's prevention policy for people with disabilities during the COVID-19 epidemic. Issue 8 (14th September 2021) - Zhang, Shubo; Chen, Zhang
Abstract: During the COVID-19 pandemic, people with disabilities are a high-risk group, but they are also the group that is most easily ignored by public policy. Non-disabled people might not be able to imagine how many barriers disabled people encountered during this challenging period. This paper focuses on the barriers encountered by people with disabilities in China and the adjustments made to public policies in response. A deeper, social-physiological factor which should also be responsible is overlooked, and that is the 'empathy deficit'. Human rights and empathetic attitudes should go hand in hand with each other when formulation and implementation of welfare security policies for persons with disabilities during a major public health crisis.